The Сontent of Some Humoral and Metabolic Vasoactive Factors in the Blood of the Cirrhotic Patients and Their Dependence on the Hepatopulmonary Syndrome Severity Degree - Abrahamovych M.; Tolopko S.; Fayura O. (Львівський клінічний вісник)
Introduction. The attempts of the different scientists to diagnose and describe dangerous pulmonary complications of chronic liver diseases were more than 100 years ago. So, in 1884, an Austrian doctor M. Fluckiger found a link between the liver diseases and lungs watching a patient with cirrhosis, cyanosis and symptom of “drumsticks.” The term “hepatopulmonary syndrome” (HPS) was ﬁrst proposed only in 1977 by a group of Swedish researchers to display the arterial hypoxemia that occurs in about 1/3 of the patients with liver cirrhosis (LC) without concomitant diseases of the cardiovascular and respiratory systems. The elucidation of the pathogenic mechanisms of HPS, taking into account its unfavorable course, small amount of symptoms, high mortality is an important task of modern hepatology and would help to diagnose it at early stages, to prevent the severity increase, using adequate pathogenetically justiﬁ ed drugs. The aim of our study was to determine the content of some humoral and metabolic vasoactive factors, namely the endothelium-dependent (cyclic guanosine monophosphate, endothelin-1, tumor necrosis factor α), indices of the renin-aldosterone system (renin, aldosterone), natriuretic hormone in the blood of the cirrhotic patients and determine their dependence on the hepatopulmonary syndrome severity degree. Materials and methods. Into the study there were involved 80 patients [23 women (28.75 %) and 57 men (71.25 %) aged 27 to 67 years old] with LC, in a randomized manner with preliminary stratiﬁ cation by the presence of HPS to achieve the aim. All of them were treated in Lviv Regional Hepatological Center for the period 2012-2015 years. Taking into account the expert assessments of the chosen characteristic features of HPS in the assessing of its severity degree (concordance coefﬁcient = 0.81; signiﬁcance was deﬁned due to R. Fischer’s criteria), we found: in case of the values from 6 to 21 points – I degree HPS, 22-43 points – II degree HPS, 44-103 points – III degree HPS. Created by us computer program “Hepatopulmonary syndrome”, which provides the selection of indices, followed by the calculation of points, helped to optimize the work with minimal time. According to this principle all the patients were stratiﬁed into three groups: the 1st group (I degree HPS) included 28 patients (35.0 %), the 2nd (I degree HPS) – 31 (38.8 %), the 3rd (I degree HPS) – 21 patients (26.3 %). The levels of some endothelium-dependent vasoactive substances in the blood plasma, indices of renin-aldosterone system and natriuretic peptide contentwere identiﬁed in all these patients. According to the results of our study there can be seen the tendency of the certain dynamics of vasoactive humoral and metabolic factors content changes in the blood of the patients with LC depending on the severity degree of HPS. The received results showed that the levels of cyclic guanosine monophosphate, tumor necrosis factor α, endothelin-1, renin, aldosterone, natriuretic peptide in the patients of the study group were signiﬁcantly higher (p < 0.05) compared with the reference rates, and the growth of their content directly proportional depends on the severity degree of lung lesions, reﬂecting endothelial dysfunction and violations of renin-aldosterone system state with the appearance of intrapulmonary vasodilation and paradoxical response of the receptors of the pulmonary vessels to the inﬂuence of vasoconstrictors that allows us to consider them as one of the pathogenic mechanisms of the HPS. Conclusions. In the patients with HPS the levels of cyclic guanosine monophosphate, tumor necrosis factor α, endothelin-1, renin, aldosterone, natriuretic peptide were signiﬁcantly (p < 0.05) higher compared with the reference values which allows us to consider them as parts of the pathogenetic mechanisms of its appearance with the activation of cascade reactions resulting in the hyperproduction of nitric oxide or direct vasorelaxation inﬂuence through the relaxation of smooth muscle cells of the vascular wall of pulmonary vessels. The value of these vasoactive humoral and metabolic factors directly proportional depends on the HPS severity degree, contributing to pre-capillary-capillary pulmonary vasodilation with the paradoxical response of the receptors of the pulmonary vessels to the inﬂuence of vasoconstrictors, and therefore can be considered as markers of lung injury severity in patients with LC.